Empowerment strategy with social capital in improving the economic, social and education of the Madura community - Yuriadi Yuriadi; Umar Faruk; Norsuhaily Abu Bakar (Jurnal Psikologi Tabularasa, 2023)
Empowerment is very important to improve the quality and quantity of the economy, social and education of the Madurese people. In this study, researchers used qualitative methods in the data collection process. The instrument in this research is the researcher himself, so that the researcher must have sufficient knowledge and insight. Data collection techniques used unstructured interviews, participant observation and technical documentation of data analysis using Cresswell’s approach. The results of the study show that empowerment from the economic sector is obtained. The community needs to obtain venture capital. Making public infrastructure and facilities must be of high quality, so they don’t break down quickly. There is training to teach entrepreneurship. The policies made by the kingdom are in accordance with the needs of the community, namely welfare. Government intervention in determining prices and processing of agricultural products must be carried out. Continuous assistance to become professional. Empowerment from the education sector is obtained, school curricula are made by involving experts. Educational programs focus on quality, collaborative and competitive. There needs to be guidance and evaluation. Collaboration between universities and government. Families need to be motivated to send their children to the highest level of education. Women need to get a chance. Empowerment from the social sector is obtained, Madurese people do not need to be afraid of different criticisms. Politics doesn’t have to be expensive. Getting used to quality life must start from the family environment. There is a collective awareness to move forward together.Pemberdayaan sangat penting untuk meningkatkan kualitias dan kuantitas ekonomi, sosial dan pendidikan masyarakat Madura. Dalam penelitian ini peneliti menggunakan metode kualitatif dalam proses pengambilan data. Instrument dalam penelitian ini ialah peneliti sendiri, sehingga peneliti harus memiliki pengetahuan dan wawasan yang memadai. Teknik pengambilan data menggunakan wawancara tidak terstruktur, observasi partisipan dan dokumentasi teknis analisis datanya menggunakan pendekatan dari Cresswell. Hasil kajian menunjukan bahawa pemberdayaan dari sektor ekonomi diper oleh Masyarakat perlu mendapatkan modal usaha. Pembuatan infrastruktur dan fasiliti umum harus berkualiti, biar tidak cepat rusak. Ada pelatihan untuk mengajarkan berwirausaha. Kebijakan yang dibuat kerajaan sesuai dengan keperluan masyarakat yaitu kesejahteraan. Intervensi pemerintah dalam menentukan harga dan pengolahan hasil pertanian harus dilakukan. Pendampingan berkelanjutan hingga menjadi professional. Pemberdayaan dari sektor pendidikan diperoleh, kurikulum sekolah dibuat dengan melibatkan ahli. Program pendidikan focus kepada kualitas, kolaboratif dan kompetitif. Perlu adanya bimbingan dan evaluasi. Kolaborasi antara universitas dan pemerintah. Keluarga perlu mendapat motivasi untuk menyekolahkan anak ke level tertinggi. Perempuan perlu mendapatkan kesempatan. Pemberdayaan dari sektor sosial diperoleh, masyarakat Madura tidak perlu takut dengan perbedaan kritikan. Berpolitik tidak harus dengan biaya mahal. Membiasakan hidup berkualitas harus di mulai dari lingkungan keluarga. Ada kesadaran kolektif untuk maju bersama.